Advances and Pitfalls in Protein Structure Prediction - Cozzetto, D.; Tramontano, A. (Current Protein and Peptide Science, 2008)
Three dimensional protein structures are crucial for understanding biology at both molecular and system level. Despite the advances in experimental structural biology, the pace of sequence deposition into databanks considerably exceeds that of structure determination. Inevitably the functional annotation of genes and genomes requires the exploitation of bioinformatics methods for protein sequence comparison and structure prediction. Hence monitoring objectively the state of art of the field is of paramount importance, in order to make best use of computational protein models to address biological questions. This review describes some relevant issues in the field of structural bioinformatics, emphasizig both open basic questions and the progress being continuously achieved. It is reasonably expected that these bioinformatics methods will increasingly contribute to the biomedical, pharmaceutical and biotechnological research.
Keywords: accuracy of sequence alignment